Relapsing–remitting clinical course expands the phenotype of Aicardi–Goutières syndrome - Jeffrey Lambe; Olwen C. Murphy; Weiyi Mu; Krista Sondergaard Schatz; Kristin W. Barañano; Arun Venkatesan (Annals of Clinical and Translational Neurology, 2020)
Abstract Aicardi–Goutières syndrome (AGS) is a rare and likely underdiagnosed genetic leukoencephalopathy, typically presenting in infancy with encephalopathy and characteristic neuroimaging features, with residual static neurological deficits. We describe a patient who, following an initial presentation at the age of 12 months in keeping with AGS, exhibited a highly atypical relapsing course of neurological symptoms in adulthood with essentially normal neuroimaging. Whole‐exome sequencing confirmed a pathogenic RNASEH2B gene variant consistent with AGS. This case highlights the expanding phenotypes associated with AGS and the potential role of whole‐exome sequencing in facilitating an increase in the rate of diagnosis.